Representasi Kesetaraan Gender dalam Kesenian Gong Waning Masyarakat Sikka Tanjung Labu Provinsi Kalimantan Timur - Arafik, Abdul Rahman; Putra, Bayu Arsiadhi; Putra, Agus Kastama (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2024)
In the Sikka community in Tanjung Labu Village, curently women have the same role as men in socio-cultural life. Inversely proportional to the social conditions in the area of origin which is closely related to patriarchal culture. This situation is even more confusing when the appointment of a woman as head of the Gong Waning art association illustrates the absence of inequality in the social life of the Sikka community in Tanjung Labu. This study uses qualitative methods with observation techniques, data collection techniques and data analysis. Observation techniques include the object of research and the determination of informants. Data collection techniques include literature study, interviews, and documentation. Lastly, the data analysis technique by utilizing field data. The results show that the form of adjustment in Gong Waning art and the social order of the Sikka people is due to adaptation and good communication between individuals in discussions that lead to the values of equality. Discussion of private issues of every individual in society is managed to become a public issue in order to find a solution. Finally, women and men are free to express their opinions explicitly without any pressure from any party. This situation ultimately forms a society that respects each other in social life.